2021
DOI: 10.3390/ani11051271
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Clinical and Radiographic Evaluation of a Novel Resorbable Implant of Polylactic Acid (PLA) for Tibial Tuberosity Advancement (TTA) by Modified Maquet Technique (MMT)

Abstract: Our objectives were to determine whether PLA implants can be used in TTA with successful results; secondly, to observe whether they provide a faster bone healing; finally, to determine whether weight or age influences bone healing scores. PLA cages were created with a 3D printer. TTA by MMT with PLA implants was performed in 24 patients. Follow-ups were carried out pre-surgical, at 1, 2, and 5 months and consisted of a radiographic study and a lameness assessment. A comparison was performed in terms of weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The results in our study demonstrated that PLA scaffolds are an acceptable alternative to metallic implants, agreeing with our preliminary study [ 37 ]. In addition, the results in our control group were better than the results obtained in other studies with the same scale in biodegradable implants [ 4 , 44 ]; moreover, our ossification results were also better than another published study with metallic implants [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results in our study demonstrated that PLA scaffolds are an acceptable alternative to metallic implants, agreeing with our preliminary study [ 37 ]. In addition, the results in our control group were better than the results obtained in other studies with the same scale in biodegradable implants [ 4 , 44 ]; moreover, our ossification results were also better than another published study with metallic implants [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The fractures had no displacement, thus they were solved by strict rest of the patient for a month, as recommended in several studies [ 3 , 52 , 62 , 63 ]; in all cases, the evolution was good and they did not require further treatment. Another minor complication was the appearance of vesicles in the area of the incision at the last follow-up, already described in our preliminary study [ 37 ]. The treatment was the application of local medication and the administration of antibiotics; the vesicles disappeared with the treatment.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations